Estudo do extrato das folhas modificadas de Euphorbia tirucalli - Desreplicação e potencial antitumoral - Russo, Daniela Cristina [UNIFESP] (2022)
Euphorbia tirucalli L., the plant selected for this research, has been popularly used to combat tumors, arousing the interest of researchers in the area of Chemistry of Natural Products. Therefore, the present study aimed to evaluate the cytotoxic activity for estrogen-positive breast adenocarcinoma (MCF-7) and anaplastic thyroid cancer (HTH83) provided by the compounds present in the methanolic extract obtained from the modified leaves. The plant was collected in the municipality of Praia Grande. After drying and grinding, chromatographic techniques were used to separate the secondary metabolites. Spectroscopic and spectrometric techniques were used to dereplicate the partitions obtained from the crude extract. The methanolic extract was used to obtain the liquid-liquid partitions with solvents of increasing polarity, hexane, dichloromethane, ethyl acetate and butanol. Due to its chemical profile, the dichloromethane partition was chosen to obtain and analyze fractions and sub-fractions. The results obtained by GC-MS and analysis by 1H and 13C NMR allowed the identification of euphol, lanosterol and tirucallol, three tetracyclic triterpenes, lupenone and lupeol, two pentacyclic triterpenes. The data obtained by LC-MS/MS in association with the Global Natural Products Social Networking (GNPS) platform allowed the annotation of fourteen substances, namely: α-adenosine; 2,3-dihydroxypropyl hexadecanoate; 13-docosenamide, (Z); chlorogenic acid; conjugated linoleic acid; palmitoleic acid; arantiamide; austinoneol; acetyl tributyl citrate; loliolide; N-fructosyl phenylalanine; N-fructosyl isoleucine; oleamide and uvaol, the latter being another pentacyclic triterpene. Cell viability assays and the calculation of the 50% effective concentration (IC50) in MCF-7 and HTH83 tumor cell lines showed promising activity, with particularly special results for sub-fractions ETD-5C2 (mixture containing lupeol) and ETD-7C2 (mixture containing eufol and tirucallol). In the first, the cytotoxic activity for HTH83 after 72 h of incubation showed IC50 equal to 9.843 µg mL-1 and in the second, the cytotoxic activity for MCF-7 after 24 h of incubation showed IC50 equal to 20.45 µg mL-1. Due to the absence in the literature of studies on thyroid cancer with the Euphorbia tirucalli species, the results of this study are complementary to recently published works and contribute to the understanding of the species and the cytotoxic activity of its metabolites.